Portrait of the Implementation of Consultation Services in Schools as Indirect Guidance and Counseling Services - Juster Donal Sinaga; Andreas Rian Nugroho (Universitas Ahmad Dahlan, 2019)
The purpose of this study is to describe the understanding of counselors in partner schools of the Sanata Dharma University Study and Counseling Program about (1) indirect guidance and counseling services; (2) consulting services; and (3) implementation of consulting services. This research method is qualitative research with case study design. Respondents of this study are couselors in 15 partner schools of the Sanata Dharma University Study and Counseling Study Program. This research data collection technique uses structured interviews. The data analysis technique used is qualitative descriptive. The results of the study showed (1) School counselors inÂ partner schools of the Guidance and Counseling Study Program at Sanata Dharma University understand the Guidance and Indirect Counseling services as (a) guidance and counseling services using media; Guidance and Counseling services that involve other people; and (c) Guidance and Counseling support services. The school counselors knowledge is not all true in accordance with the theories and concepts of Guidance and Counseling services; (2) School counselors inÂ partner schools of the Guidance and Counseling Study Program at Sanata Dharma University understand consulting services as services by counselor as consultants to students as consultants, services by counselor as consultants to others as consultants, and services by expert as consultants to school counselors as a consultant; and (3) School counselors inÂ partner schools of the Guidance and Counseling Study Program at Sanata Dharma University carry out consulting services from planning to evaluation in a systematic and not well conceptualized manner. The School counselors carry out consultation services if there are parents or teachers coming